PENGETAHUAN DAN PEMAHAMAN DINI NARKOBA DAN ZAT ADITIF PADA GENERASI MUDA SEBAGAI ASET BANGSA DI DESA MENGWI BADUNG - Suaniti, N.M.; Wirajana, I.N.; Ariati, N.K.; Manurung, M. (Buletin Udayana Mengabdi, 2017)
The era of globalization is an opportunity and challenges Indonesian youths to participate actively obtain in things that are not good, one of them understood early knowledge of drugs and additives that enable the younger generation can be misleading. Drugs (narcotics and drug/ hazardous materials) with another term drug (narcotics, psychotropic and other addictive substances) by the Ministry of Health of the Republic of Indonesia refers to a group of compounds generally have a risk of addition for users. Furthermore, food additives can also cause poisoning. Badung is one of part of the world where tourist destinations Mengwi village is connecting northern and southern regions become vulnerable to the effects of prevention efforts of prevention efforts undertaken so that one of them by giving lectures drugs and additives by the relevant authorities. The method is performed by giving a lecture and question and answer session with filling out the questionnaire pre and posttest. The results of the questionnaire were analyzed and showed an increase understanding of drugs and additives significantly to the spread evenly on the younger generation in Mengwi village after the activity, but this dedication activities need to be carried out periodically in each row and expanded in other rural communities in Bali